1987
DOI: 10.1073/pnas.84.19.6953
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptide homologous to beta protein from Alzheimer disease forms amyloid-like fibrils in vitro.

Abstract: Progressive amyloid deposition in senile plaques and cortical blood vessels may play a central role in the pathogenesis of Alzheimer disease. We have used x-ray diffraction and electron microscopy to study the molecular organization and morphology of macromolecular assemblies formed by three synthetic peptides homologous to fi protein of brain amyloid: fl-(1-28), residues 1-28 of the fi protein;[Ala"Jfl-(1-28), P-(1-28) with alanine substituted for lysine at position 16; and fl-(18-28), residues 18-28 of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
418
5
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(453 citation statements)
references
References 29 publications
29
418
5
1
Order By: Relevance
“…These octamers add relatively slowly to protofilament ends yielding long thin 5-nm filaments, which can associate laterally to form ribbons. All of these structures are observed in electron micrographs of naturally occurring amyloid fibrils and are similar or slightly smaller than synthetic amyloid fibrils (Kirschner et al, 1987;Fraser et al, 1991;Hilbich et al, 1991). The kinetics of the peptide aggregation process monitored by the light scattering technique suggest that in such a reaction scheme ThT would probably bind to an oligomeric form such as the octamer since the fluorescence enhancement is observed within seconds after aggregation is initiated, and it is not observed to be effected by the subsequent slower addition of octamers at filament ends.…”
Section: Discussionmentioning
confidence: 89%
“…These octamers add relatively slowly to protofilament ends yielding long thin 5-nm filaments, which can associate laterally to form ribbons. All of these structures are observed in electron micrographs of naturally occurring amyloid fibrils and are similar or slightly smaller than synthetic amyloid fibrils (Kirschner et al, 1987;Fraser et al, 1991;Hilbich et al, 1991). The kinetics of the peptide aggregation process monitored by the light scattering technique suggest that in such a reaction scheme ThT would probably bind to an oligomeric form such as the octamer since the fluorescence enhancement is observed within seconds after aggregation is initiated, and it is not observed to be effected by the subsequent slower addition of octamers at filament ends.…”
Section: Discussionmentioning
confidence: 89%
“…In vitro experiments have provided evidence supporting the capability of a large variety of proteins and peptides, including those unrelated to any disease, to self-assemble into amyloid fibrils or amyloid-like structures when incubated under appropriate solution conditions. This has led to the suggestion that the ability to form amyloid fibrils is a fundamental property of polypeptide chains (Glenner et al 1974;Kirschner et al 1987;Maggio and Mantyh 1996;Fändrich and Dobson 2002;Makin and Serpell 2005;Chiti and Dobson 2006;Goldschmidt et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The -(1-42) peptide adopts 100% oligomeric -sheet structure in solution before it precipitates as an amyloidlike, oligomeric -pleated sheet structure (Kirschner et al, 1987;Barrow et al, 1992). Once the precipitation starts, the solution conformation will remain 100% -sheet and the ellipticities will decrease in amplitude since the peptide concentration in solution decreases.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The -(1-28) peptide is an appropriate structural model for the complete -(1-42) peptide, since it produces soluble monomeric R-helical structures (Barrow & Zagorski, 1991;Otvos et al, 1993), as well as plaque-like oligomeric -sheet structures, similar to those found in natural amyloid plaques (Gorévic et al, 1987;Kirschner et al, 1987). The hydrophobic 29-42 region increases the rate of aggregation and -sheet production (Hilbich et al, 1991;Barrow et al, 1992;Burdick et al, 1992; but should not affect the ability of nicotine to bind to the -peptide.…”
Section: Shown Inmentioning
confidence: 99%
See 1 more Smart Citation